The design of expert system to determine the university majoring based on multiple intelligence using forward chaining method - Fan Folkourng; Rizki Hardian Sakti (Journal of Engineering Researcher and Lecturer, 2022)
An expert system is one of artificial intelligence that uses a computer to work like and as well as humans do. An expert system is a computer system that is designed so that it has the ability and reasoning like an expert. But, the expert system is not used for replacing an expert who in this problem im a psychologist as a consultant for students want to recognize the potential and their abilities. The expert system is only used as equipment and limited tools. There is a problem is how to design tools to help students recognize their potential and abilities, so that they can choose the right department in the University based on their potential and abilities. Expert system design for assign department in the University based Multiple Intelligence use visual basic programming language and Microsoft Office Access as database.